Religious Piety as Commodity: Political Economy of Muslim Women’s Consumption in Hijabersmom Community (HMC) - Nursyafa’ah, Ati'; Musadad, Ahmad; Noor Azizah, Auli Fisty; Pujiati, Tri; Fauzi, Alfa Zaidanil (UAS PRESS, 2026)
The culture of consumption among contemporary Muslims demonstrates that religious expression is no longer confined to ritual observance but is increasingly manifested through symbols, Islamic lifestyles, and consumption choices that affirm particular forms of religious identity. While previous scholarship has extensively examined Muslim consumption in relation to religiosity, halal products, and Islamic fashion, limited attention has been devoted to understanding religious piety as a commodity constructed through everyday consumption practices. This study seeks to critically examine how values of piety are socially constructed and how the mechanisms of religious commodification operate within a Hijabersmom Community (HMC) in Deltasari, Sidoarjo. To capture this social reality, the study employs a qualitative-interpretive approach through participant observation, in-depth interviews, and the examination of community documents. Theoretically, the analysis is situated within a political economy framework by synthesizing perspectives on the commodification of religion, consumption practices among the Muslim middle class, and the expanding dynamics of the Islamic lifestyle economy. The findings indicate that the construction of piety within the community manifests through three principal dimensions: ritual observance, social relations (muamalah), and symbolic expression, particularly through the adoption of shar‘i fashion as a marker of collective identity. Furthermore, the community functions not merely as a spiritual sanctuary but also as a dynamic economic arena in which commodities, including Muslim fashion, culinary products, and household necessities, are exchanged among members. This study concludes that contemporary religious communities increasingly operate as hybrid social spaces where spirituality, middle-class identity, and economic interests intersect within the everyday lives of urban Muslim women.